Updating Reservoir Models Using Ensemble Kalman Filter - Sutawanir Darwis; AGUS YODI GUNAWAN; SRI WAHYUNINGSIH; NURTITI SUNUSI; ACENG KOMARUDIN MUTAQIN; NINA FITRIYATI (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2010)
The Ensemble Kalman Filter (EnKF) has gain popularity as a methodology for real time updates ofreservoir models. A sample of models is updated whenever observation data available. Successfulapplication of EnKF to estimate reservoir properties has been reported. A flow modeling is missing inthis research area. This paper presents the applicability of EnKF in flow modeling for three cases:infinite reservoir, bounded reservoir and one dimensional composite reservoir. The solution of flowequation was derived and used as a modeling component of state space modeling of Kalman filterupdating formula. This three reservoir models shows that the EnKF methodology can be used forupdating the reservoir models.